Baseline endometriosis-associated pain burden: Data from 1600+ women enrolled in elagolix clinical trials. Issue 3 (September 2019) - Leyland, Nicholas; Estes, Stephanie J; Eichner, Samantha; Soliman, Ahmed M; Mai, Yabing; Snabes, Michael C; Taylor, Hugh S; Surrey, Eric S
Background: The daily pain burden experienced by women with endometriosis has not been well studied. Objective: To characterize baseline pain among women with moderate-to-severe endometriosis-associated pain enrolled in phase 3 studies of elagolix, an oral, nonpeptide gonadotropin-releasing hormone antagonist. Study design: Data were pooled from the screening phase of two randomized, double-blind, placebo-controlled clinical trials. After cessation of endometriosis medications, patients entered the screening phase during which symptoms (dysmenorrhea, nonmenstrual pelvic pain, and dyspareunia) and rescue medication use were recorded daily in electronic diaries. Endometriosis-associated pain was also scored using the Numeric Rating Scale (range 0–10). Baseline was defined as the last 35 days during the screening period. Results: Endometriosis-associated pain was reported by the 1686 study participants on most days during the baseline interval. Pain was often moderate or severe, with a mean Numeric Rating Scale score of 5.6 ± 1.7. Women reported dysmenorrhea an average of 8.1 ± 3.0 days (97.9% ± 7.0% of menstruating days), nonmenstrual pelvic pain on 20.5 ± 5.4 days (90.3% ± 15.8% of nonmenstruating days), and dyspareunia on 8.7 ± 8.0 days (81.7% ± 29.7% of sexually active days). When they occurred, dysmenorrhea, nonmenstrual pelvic pain, and dyspareunia were frequently moderate or severe in intensity. Women were free of pelvic pain for an average of 2.4 ± 3.9 days during the 35-day evaluation interval. Conclusion: Among women with untreated moderate-to-severe endometriosis pain, the daily burden of pain was extensive, both during menstruation and on nonmenstruating days.